2018
DOI: 10.5607/en.2018.27.6.489
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1 Receptor Dictates Beneficial Effects of Treadmill Training by Regulating Survival and Migration of Neural Stem Cell Grafts in the Injured Spinal Cord

Abstract: Survival and migration of transplanted neural stem cells (NSCs) are prerequisites for therapeutic benefits in spinal cord injury. We have shown that survival of NSC grafts declines after transplantation into the injured spinal cord, and that combining treadmill training (TMT) enhances NSC survival via insulin-like growth factor-1 (IGF-1). Here, we aimed to obtain genetic evidence that IGF-1 signaling in the transplanted NSCs determines the beneficial effects of TMT. We transplanted NSCs heterozygous (+/−) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In one study, it was shown that increasing the concentration of IGF-1 in the cerebrospinal fluid, along with treadmill training, could markedly attenuate reactive nitrogen or oxygen species, which are detrimental to NSC survival after transplantation. Moreover, Hwang and colleagues found that mice receiving IGF-1R +/- NSC grafts showed reduced locomotor recovery compared with those receiving wild-type (IGF-1R +/+ ) NSCs, illustrating that IGF-1 R plays an important role locomotor recovery 52 . In our study, we found the level of IGF-1 R in the rostral segment was increased significantly after transplanting NSCs in the site of the SCT.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was shown that increasing the concentration of IGF-1 in the cerebrospinal fluid, along with treadmill training, could markedly attenuate reactive nitrogen or oxygen species, which are detrimental to NSC survival after transplantation. Moreover, Hwang and colleagues found that mice receiving IGF-1R +/- NSC grafts showed reduced locomotor recovery compared with those receiving wild-type (IGF-1R +/+ ) NSCs, illustrating that IGF-1 R plays an important role locomotor recovery 52 . In our study, we found the level of IGF-1 R in the rostral segment was increased significantly after transplanting NSCs in the site of the SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Serum-free suspension culture with EGF-and bFGF-containing medium led to a significant increase in neurogenic and stemness gene expression (probably neurogenic genes predominate) in UC-MSCs, resulting in neurosphere formation which closely resembles neural progenitor cells with self-renewal and multipotency capacity. IGF all have been implicated in neural stem cell maintenance and proliferation [36][37][38][39][40][41], and thus they can be seen as at least partially neurogenic cytokines. Therefore, our short neural induction protocol not only produced cell phenotypically resembling neurospheres but also led to a quick upregulation and expression of neurogenic and angiogenic cytokines.…”
mentioning
confidence: 99%
“…The exercise schedule was started 1 week after injury, and treadmill exercise was performed twice per day (morning and afternoon for 15 min per session) and 5 days per week for 12 weeks after injury ( Figure 1 ). Treadmill exercise was conducted at a running speed of 5 m/min at the beginning, and the speed was gradually increased to 12 m/min as the walking capabilities of the rats allowed until the end of the training as previously described [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%